Homelessness and substance misuse: impact on secondary healthcare in Wales - James, Delyth; Colonna, Silvia; Farr, Ian; Evans, Hywel; Dixon, Josh; Matthew, Skermer; Fallick, Sam; Davies, Gareth; Ohaeri, Columbus; Smith, Josie (International Journal of Population Data Science, 2025)
Objectives This study examined the relationship between co-occurring homelessness and substance misuse and the use of secondary healthcare in Wales. The study was carried out as part of the Better Outcomes through Linked Data (BOLD) Substance Misuse Pilot Wales, which focuses on early intervention and prevention of escalation of substance misuse. Methods The study used routinely collected administrative data from the Secure Anonymised Information Linkage (SAIL) Databank. Datasets used include primary care, hospital admissions, emergency department and specialist substance misuse treatment. We identified a cohort of over 32,000 Welsh residents who were in substance misuse treatment between 2014 and 2019. The analysis looked at the relationship between co-occurring homelessness and substance misuse in relation to the frequency of emergency department attendances the reasons for emergency hospital admissions the frequency of hospital admissions the length of hospital admissions We also looked at how homelessness, types of substance misuse, and demographics interacted. Results For the individuals in substance misuse treatment, homelessness was associated with: an increase in the number of times an individual would be expected to attend an emergency department an increased likelihood that an individual would be admitted to hospital as an emergency an increase in the number of times an individual would be expected to be admitted to hospital an increased likelihood of emergency hospital admissions for certain diagnoses, including: injury and poisoning mental and behavioural disorders skin diseases an increase in the expected duration of hospital admissions. Conclusion This study highlights the health impacts of co-occurring homelessness on individuals in substance misuse treatment, showing how people facing multiple disadvantages, like homelessness and substance misuse, experience profound health inequalities. Understanding how people with these co-occurring conditions access health services could help healthcare providers better plan support for those individuals.